Social forestry in Southeast Asia: Evolving interests, discourses and the many notions of equity - Wong, Grace Y.; Moeliono, M.; Bong, I.W.; Pham Thu Thuy; Sahide, M.A.K.; Naito, D.; Brockhaus, Maria (Elsevier, 2020)
Southeast Asia has long promoted social forestry (SF) in conservation areas, fallow forests, tree plantations, areas in timber concessions and locally managed agro-forest systems, with the engagement of diverse actors and objectives. SF has evolved from early aims of empowerment and devolution of rights advocated by global reform movements, and is now reframed in the market ideal as a win–win–win endeavor for sustainable forest management, climate change mitigation and robust entrepreneurial livelihoods. Southeast Asian states have formulated numerous standardized SF programs and policies that are often linked to broader development goals and priorities, but which have not always been a ‘win’ for local communities in falling short to provide full tenure rights. Civil society organizations that have provided grounded perspectives on environmental justice and rights have also converged with states on entrepreneurship and market-based solutions. Meanwhile, the private sector actor that is seen as key to these solutions is conspicuously absent within the SF policy space. Within this space of diverse and at times contradictory objectives, whose interests do SF policies serve? We examine the social forestry assemblage to investigate the different discourses, interests and agendas in the implementation of SF schemes in Indonesia, Vietnam, and the Malaysian state of Sabah. The formal SF schemes involve shifting or reinforcing old discourses around forest problems and possible solutions, territorialization processes that can lead to inequities in the exclusion of rights, participation and access, and risks exacerbating contestations and inequities in claims to forest land and resources.